Renal- and calcium-dependent vascular effects of Polybia paulista wasp venom - Vinhote, J. F.C. (2011)
In the present study, the effects of Polybia paulista venom (PPV) on renal and vascular tissues were investigated. Isolated kidneys perfused with PPV (1 and 3 μg/mL) had increased perfusion pressure, renal vascular resistance, urinary flow, and glomerular filtration rate; and reduced sodium tubular transport. Histological evaluation demonstrated deposits of proteins in Bowman's space and tubular lumen, and focal areas of necrosis. The venom promoted a cytotoxic effect on Madin-Darby canine kidney (MDCK) cells. A significant increase in lactic dehydrogenase levels was observed in response to venom exposure. In isolated mesenteric vascular beds, pressure and vascular resistance augmented in a dose-dependent manner. PPV increased the contractility of aortic rings maintained under basal tension. This contractile response was inhibited when preparations were maintained in Ca2+-free medium. Likewise, verapamil, a voltage-gated calcium channel blocker, also inhibited the contractile response. In this study, phentolamine, a blocker of α-adrenergic receptor blocker, significantly reduced the contractile effect of PPV in the aortic ring. In conclusion, PPV produced nephrotoxicity, which suggests a direct effect on necrotic cellular death in renal tubule cells. The vascular contractile effect of PPV appears to involve calcium influx through voltage-gated calcium channels via adrenergic regulation. © CEVAP 2011.